2013
DOI: 10.1242/dev.088328
|View full text |Cite
|
Sign up to set email alerts
|

Pax7 is regulated by cMyb during early neural crest development through a novel enhancer

Abstract: SUMMARYThe neural crest (NC) is a migratory population of cells unique to vertebrates that generates many diverse derivatives. NC cells arise during gastrulation at the neural plate border (NPB), which is later elevated as the neural folds (NFs) form and fuse in the dorsal region of the closed neural tube, from where NC cells emigrate. In chick embryos, Pax7 is an early marker, and necessary component of NC development. Unlike other early NPB markers, which are co-expressed in lateral ectoderm, medial neural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
(90 reference statements)
0
13
0
Order By: Relevance
“…In addition, transcription factors Myb, Myc, and Prdm1 are also required for specification [4244]. Myb directly interacts with Pax3/7 as well as Sox10 in chick, and Prdm1 directly interacts with Tfap2a and Foxd3 in fish [4346]. …”
Section: Neural Crest Specificationmentioning
confidence: 99%
“…In addition, transcription factors Myb, Myc, and Prdm1 are also required for specification [4244]. Myb directly interacts with Pax3/7 as well as Sox10 in chick, and Prdm1 directly interacts with Tfap2a and Foxd3 in fish [4346]. …”
Section: Neural Crest Specificationmentioning
confidence: 99%
“…cMyb is known to regulate Pax7 expression in chick at neural plate border stages (Vadasz et al, ), and was also found to regulate the expression of the neural crest specifier snai2 (Karafiat et al, ). Gene expression analysis following cMyb knockdown in chick revealed downregulation of Pax7 and Twist1 , among others, and an upregulation of Zic1 (Betancur, Simões‐Costa, Sauka‐Spengler, & Bronner, ), placing cMyb as a regulator of neural plate border and neural crest specifier genes.…”
Section: Transcriptional Network Underlying Neural Crest Cell Formationmentioning
confidence: 99%
“…The direct regulation of Pax7 expression is a major question. In chick, this has been shown to occur through cMyb binding to a Pax7 enhancer (Vadasz, Marquez, Tulloch, Shylo, & Garcia-Castro, 2013), and studies in Xenopus indicate that Pax3 directly activates its own expression and that of pax7 (Maczkowiak et al, 2010;Plouhinec et al, 2014).…”
Section: Neural Plate Border Specifiersmentioning
confidence: 99%
“…In this assay, Hamburger-Hamilton stage 11 embryos are electroporated with DNA reporter constructs in which the putative enhancer is cloned upstream of a minimal promoter driving EGFP expression (see Materials and Methods ). This assay has been previously used to validate enhancers for multiple signaling pathways [ 20 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Endogenous Sonic Hedgehog (SHH) produced by the notochord and floorplate drives expression of Hh-dependent enhancers in the ventral half of the neural tube [ 53 ].…”
Section: Resultsmentioning
confidence: 99%